2017
DOI: 10.5194/hess-21-5531-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating climate change impacts on streamflow variability based on a multisite multivariate GCM downscaling method in the Jing River of China

Abstract: Abstract. Projected hydrological variability is important for future resource and hazard management of water supplies because changes in hydrological variability can cause more disasters than changes in the mean state. However, climate change scenarios downscaled from Earth System Models (ESMs) at single sites cannot meet the requirements of distributed hydrologic models for simulating hydrological variability. This study developed multisite multivariate climate change scenarios via three steps: (i) spatial do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…[15] found that climate change would significantly influence the hydrology of two subbasins in the upper Nile in Ethiopia. [16] in their study also found increasing streamflow variability attributed to increasing rainfall variability in the Jing River of China. [17], in their study, projected an arid-conditions by the 2080s for many subbasins in the Upper Colorado River Basin of the southwestern United States when they investigated the impacts of Climate Change on Streamflow and hydrology of the basin.…”
Section: Introductionmentioning
confidence: 71%
“…[15] found that climate change would significantly influence the hydrology of two subbasins in the upper Nile in Ethiopia. [16] in their study also found increasing streamflow variability attributed to increasing rainfall variability in the Jing River of China. [17], in their study, projected an arid-conditions by the 2080s for many subbasins in the Upper Colorado River Basin of the southwestern United States when they investigated the impacts of Climate Change on Streamflow and hydrology of the basin.…”
Section: Introductionmentioning
confidence: 71%
“…But, the flows do not seem to find the levels observed before the dryness which sufferedcentral and western Africa in the years 1950 [32]. This prediction seems contrary with that envisaged by [3] at the end of this century in two rivers in Ethiopia and by [2] in the Jing river in China.…”
Section: Evolution Of Streamflowsmentioning
confidence: 98%
“…Taking into account the impacts of the climate change on the hydrological resources in a catchment aera and sometimes its dramatic consequences, the evolution of water resources becomes a major concern for many countries inthe world [1][2][3][4][5][6][7][8]. This is all the more true for the african countries, particularly those of the sahelianzone, subjected since more than one half-century, with a persistent dryness [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Climate model datasets, which are derived from general circulation model (GCM), can provide future rainfall and temperature. The evaluation of the Coupled Model Intercomparison Project Phase 5 (CMIP5) climate dataset shows that temperature and rainfall can be well simulated in the Yangtze basin and Qinghai-Tibet Plateau [21][22][23]. Since the dataset is similar to the actual situation, CMIP5 is suitable for large regional climate change simulation.…”
Section: Introductionmentioning
confidence: 99%